The Effect of Digital Storytelling Usage on Students’ Speaking Ability at Grade XI of SMA Negeri 1 Aek Songsongan Academic Year 2021/2022 - Auliya, Maya; Siregar, Nurhafni (Medan Resource Center, 2022)
The objective of the research was to determine whether there was a significant effect of the use digital storytelling on the speaking ability of the students n XI grade at SMA Negeri 1 Aek Songsongan . This research was a quantitative research. It was conducted in XI grade at SMA Negeri 1 Aek Songsongan in the academic year 2021/2022. The total population was 124 students and researcher took 30 students for the experimental group and 30 students for the control class which meant 60 students as a total sample. In collecting data, researcher used orraly tests by speaking to retell the summary of the story as instruments. Tests were pre-tests given before treatment and post tests given after treatment. Then, the data obtained were analyzed by applying the t-test formula. The researcher found that the post–test mean score in the experiment group was higher than the control group. The results showed that the t-observe was higher than t-table (4.07 > 1.68) at a significant level of 0.05 and the degree of freedom (df) was 58. The null hypothesis (H0) was rejected and the alternative (Ha) was accepted. Thus, the use of the digital storytelling has a signficant effect on students’ speaking ability in the XI grade students of SMA Negeri 1 Aek Songsongan.